2016
DOI: 10.1111/coa.12607
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between hearing impairment and cognitive function: a meta‐analysis in adults

Abstract: This meta-analysis suggests that hearing impairment is associated with cognitive problems. However, due to diversity within studies, small sample sizes, the failure to control for premorbid and other health factors, this conclusion may be premature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
145
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(164 citation statements)
references
References 34 publications
5
145
0
7
Order By: Relevance
“…Subsequently, it is recommended that future studies draw from the experience of the field of cognitive psychology, especially from studies investigating emotional disorders such as chronic pain and anxiety where attentional biases can impact upon cognition (Andersson et al, 2005), and from studies exploring the relationship between hearing loss and cognition (Taljaard et al, 2016). Future studies exploring the relationship between tinnitus and cognition need to employ strategies that evaluate cognitive function, and control for, or account for, confounding variables.…”
Section: Limitations and Directions For Future Studymentioning
confidence: 99%
“…Subsequently, it is recommended that future studies draw from the experience of the field of cognitive psychology, especially from studies investigating emotional disorders such as chronic pain and anxiety where attentional biases can impact upon cognition (Andersson et al, 2005), and from studies exploring the relationship between hearing loss and cognition (Taljaard et al, 2016). Future studies exploring the relationship between tinnitus and cognition need to employ strategies that evaluate cognitive function, and control for, or account for, confounding variables.…”
Section: Limitations and Directions For Future Studymentioning
confidence: 99%
“…The degree of cognitive impairment (especially in memory and executive function) associated with HL is clinically significant; a 25 dB HL is associated with a reduction in cognitive performance equivalent to an age difference of 7 years [5]. A meta-analysis of 33 studies demonstrated a medium effect size (Cohen's d = 0.54) of the association of HL with cognitive impairment across all domains of cognition [4]. The potential implications for HL interventions are several.…”
Section: Discussionmentioning
confidence: 99%
“…Taljaard et al [4] found that hearing intervention significantly improved cognition ( d = 0.49, small effect) in a recent meta-analysis, though they comment that this may be attributable to reasons other than improvement in cognition, such as increased audibility of auditory tests or reduced cognitive load. The effect has been documented following both hearing aid use and cochlear implantation [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work, including a meta-analysis of 33 studies [6], reported that SNHL is independently related to both cognitive impairment [7] and the risk of incident dementia [4], and perhaps most critically, that the degree of hearing loss predicts both the degree of cognitive impairment [1] and risk of dementia [4]. Furthermore, recent work suggests that 9% of dementia risk over the life-course could be eliminated by avoiding the effects of hearing loss [5].…”
Section: Introductionmentioning
confidence: 99%